Immune Modulation Effects of Lactobacillus casei Variety rhamnosus on Enterocytes and Intestinal Stem Cells in a 5-FU-Induced Mucositis Mouse Model - Chun-Yan Yeung; Jen-Shiu Chiang Chiau; Mei-Lien Cheng; Wai-Tao Chan; Szu-Wen Chang; Chuen-Bin Jiang; Hung-Chang Lee (Gastroenterology Research and Practice)
Background. Intestinal mucositis remains one of the most deleterious side effects in cancer patients undergoing chemotherapy. We hypothesize that the probiotics could preserve gut ecology, ameliorate inflammation, and protect epithelia via immune modulations of enterocytes and intestinal stem cells. Our aim is to characterize these changes and the safety of probiotics via a 5-fluorouracil- (5-FU-) induced intestinal mucositis mouse model. Methods. 5-FU-injected BALB/c mice were either orally administrated with saline or probiotic suspension of Lactobacillus casei variety rhamnosus (Lcr35). Diarrhea scores, serum proinflammatory cytokines, and T-cell subtypes were assessed. Immunostaining analyses for the proliferation of intestinal stem cells CD44 and Ki67 were processed. Samples of blood and internal organs were investigated for bacterial translocation. Results. Diarrhea was attenuated after oral Lcr35 administration. Serum proinflammatory cytokines were significantly increased in the 5-FU group and were reversed by Lcr35. A tremendous rise of the CD3+/CD8+ count and a significant decrease of CD3+CD4+/CD3+CD8+ ratios were found in the 5-FU group and were both reversed by Lcr35. 5-FU significantly stimulated the expression of CD44 stem cells, and the expression was restored by Lcr35. 5-FU could increase the number of Ki67 proliferative cells. No bacterial translocation was found in this study. Conclusions. Our results showed that 5-FU caused intestinal inflammation mainly via Th1 and Th17 responses. 5-FU could stimulate stem cells and proliferation cells in a mouse model. We demonstrate chemotherapy could decrease immune competence. Probiotics were shown to modulate the immune response. This is the first study to analyze the immune modulation effects and safety of Lactobacillus strain on enterocytes and intestinal stem cells in a mouse model.